A influência das políticas públicas nos processos de democratização do acesso e internacionalização do ensino superior brasileiro - Egreggio, André Luís (2016)
The objective of the survey resided in understanding the extent to which public policies in Brazil, in the last 10 years, have influenced the processes of democratization of access and internationalization of Higher Education. From a historical perspective, one sought to understand the limitations of the Brazilian educational system, focusing on its institutional dynamics and the context of the expanding access and internationalization as key elements, from the point of view of the contemporary society, based on information and knowledge. The deployed methodological resources involved the qualitative approach, the adoption of the comprehensive method and the exploration of bibliographic sources, documentary and field. In line with the approach and the method chosen, the field research was conducted through interviews, granted by professors-researchers with qualified experience in higher education. The treatment of the resulting data from the interviews respected the procedures recommended by the technique of content analysis. The results showed that the public policies adopted in the course of the last democratic Governments, especially the Governments of Presidents Lula and Dilma, generated some programs - Fies, Prouni and Reuni - directly responsible for the significant growth in registration in Higher Education from young people and adults, from different social economic categories. Despite the expansion of access to Higher Education, one found that the increase in the number of vacancies occurred predominantly in the private sector. Moreover, just recently, it was accompanied by measures that sought to balance the growth of registration and the quality of teaching and learning. Aligned to the policies of democratization, in the field of internationalization of higher education, the federal Government has invested considerable sums in both the creation and consolidation of two federal universities that started internationally (Unila and Unilab), as in the opening of the program Science Without Borders. Without disregard to the relevance of these initiatives, it is worth noting that the implementation of these policies still lacks studies whose results are capable of revealing the results achieved in terms of the desired impacts, i.e. What are the gains given to the Brazilian society?